Hypertension. (July 2022) - Adeyeye, Elizabeth; Kapil, Vikas; Lobo, Melvin D
Abstract: Hypertension is one of the most prevalent modifiable conditions contributing to global morbidity and mortality. It is a risk factor for cardiovascular and renal disease as well as cognitive decline and premature death. In the UK, hypertension affects around a quarter of adults and accounts for 1 in 8 consultations in primary care. Despite the wide availability of suitable medicines, only approximately 21% of hypertensive patients have their blood pressure adequately controlled. Effective management of hypertension mandates assessment for target organ damage and potential secondary causes. Accurate blood pressure measurement is crucial for diagnosis and can require recordings to be made in the clinic and at home, as well as using ambulatory methods. Treatment depends on both blood pressure level and total cardiovascular risk. Evidence-based treatment algorithms exist to simplify the approach to treatment, and most patients require at least two medications to achieve adequate control. Severely elevated blood pressure can lead to acute organ failure that requires emergency treatment. Routine management of hypertension relies on careful combinations of different classes of drugs and titration of dosage, as well as patient education, lifestyle modifications and adherence to therapy.